International Fisheries Agreements with a Shifting Stock - Diekert, Florian; Nieminen, Emmi (Dynamic games and applications, 2017)
When a fish stock shifts from one nation to another nation, e.g., due to climate change, the nation that loses the resource has incentives to deplete it, while the other nation, receiving the resource, has incentives to conserve it. We propose an analytical model to study under which circumstances self-enforcing agreements can align incentives. Our setup allows to distinguish between a fast and a slow shift and between a smooth or a sudden shift in ownership. We show that the shorter the expected duration of the transition, the higher the total equilibrium exploitation rate. Similarly, a sudden shift implies—by and large—more aggressive non-cooperative exploitation than a gradual shift. However, a self-enforcing agreement without side-payments is more likely for a sudden than for a smooth shift. Further, the scope for cooperation increases with the expected duration of the transition, and it decreases with the renewability of the resource and the discount rate. Most importantly, we show that concentrating on in-kind transfers can be very detrimental for shifting renewable resources: In some cases, there is no efficient bargaining solution without side-payments, even when there are only two players.
Published online: 23 March 2016
Gesehen am 13.05.2019